PENGARUH PDRB PER KAPITA, PENDIDIKAN IBU, DAN PELAYANAN KESEHATAN TERHADAP ANGKA KEMATIAN BAYI DI PROVINSI BALI - Warsita, Wika Manda; Marhaeni, AAIN (PIRAMIDA, 2015)
Economic progress, environmental improvement, and the advancement of science, mainly due to the advances of medical science, were able to reduce infant mortality. This study aimed to analyze the effect of GDP per capita, mother’s level of education and health care proxy with the medical delivery against infant mortality. The data used in this study is secondary data for 23 years were obtained from various sources such as CPM and the Bali Provincial Health Department. The analysis technique used is multiple linear regression analysis techniques. Based on the analysis it was found that the variable GDP per capita has negative effect but not significant on infant mortality. Variable levels of maternal education and health care variables are proxied by the medical delivery and significant negative effect on infant mortality. This means that the higher the mother’s education and medical delivery the infant mortality rate will decrease. GDP per capita have a negative effect but not significant effect on infant mortality, however, the government is expected to continue to develop programs to revitalize the economy. Mother’s education and medical delivery and significant negative effect therefore the government is expected to provide scholarships for poor women and expanding medical delivery in all regions of the province of Bali. The government is also expected to continue to be consistent in the development program of clean water and drinking water quality, provision of vitamins, infant immunization, and provide socialization clean and healthy lifestyle behaviors to reduce infant mortality and achievement of the MDGs in Bali Province.
Keywords: infant mortality rate; social demographic; social economic; Millennium Development Goals (MDGs)